Memorandum of understanding between Universiti Teknologi MARA and Universitas Muhammadiyah Purwokerto, Indonesia / Fakulti Farmasi - Universiti Teknologi MARA, Fakulti Farmasi (Universiti Teknologi MARA (UiTM), 2017)
UiTM and Universitas Muhammadiyah Purwokerto endeavour to take necessary steps to encourage and promote cooperation.